The long walk home [videorecording (DVD)] - Spacek, Sissy; Goldberg, Whoopi, 1955-; Schultz, Dwight; Rhames, Ving, 1961-; Steenburgen, Mary (2013)
Odessa Cotter, is a quiet, dignified woman who works as a housekeeper for Miriam Thompson. When Odessa honors the 1955 Montgomery, Alabama, bus boycott by walking an exhausting nine miles to and from work, Miriam offers her a ride. Defying both Miriam's racist husband, and the powerful White Citizen's Council, Miriam and Odessa put their lives in danger for civil rights.